The Role Of Budgeting In Facing Economic Dynamics In The Digital Era - Asyraf Ubaidillah; Chaerul Sani (Penerbit Hellow Pustaka, 2025)
The digital era has brought significant changes to the global economic structure, so a more strategic financial approach is needed, one of which is through budget management. Budget management plays an important role in helping individuals and businesses optimize financial resources, so that they can adapt to ongoing economic changes. This article discusses the importance of budget management, strategies for implementing it, and the various challenges that arise in the digital era. By understanding this concept, readers are expected to be able to improve their ability to manage finances to achieve economic stability and sustainability.